Implementación de un sistema basado en sensores inerciales para la caracterización biomecánica de la marcha normal y de pacientes con amputación del miembro inferior (2021)
People with lower limb prostheses have limited mobility and possible gait disturbance. The use of inertial sensors can support the biomechanical characterization of these alterations. The present work seeks to implement a system based on inertial sensors, which allows the biomechanical characterization of the gait patterns of people with lower limb prostheses and to obtain quantitative information for a timely intervention by health personnel. Two experiments were conducted in this project, one for the validation of the reliability of the system and the other for the quantification of gait asymmetry. For the validation, a comparison between two motion analysis systems, an optical system and the system based on inertial sensors, was presented. When the comparison was made to quantify the similarity, it was found that the system based on inertial sensors used in this research has an acceptable accuracy. In the gait asymmetry studies, three adults with a healthy gait and one with an impaired gait were studied. Additionally, a kinematic database of people with transfemoral prosthesis was used, from which the data of two subjects were used to compare with the results obtained in this project.